2012
DOI: 10.1261/rna.031286.111
|View full text |Cite
|
Sign up to set email alerts
|

An energetically beneficial leader–linker interaction abolishes ligand-binding cooperativity in glycine riboswitches

Abstract: Comprised of two aptamers connected by a short nucleotide linker, the glycine riboswitch was the first example of naturally occurring RNA elements reported to bind small organic molecules cooperatively. Earlier works have shown binding of glycine to the second aptamer allows tertiary interactions to be made between the two aptamers, which facilitates binding of a separate glycine molecule to the first aptamer, leading to glycine-binding cooperativity. Prompted by a distinctive protection pattern in the linker … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
85
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(95 citation statements)
references
References 45 publications
(74 reference statements)
10
85
0
Order By: Relevance
“…In the presence of glycine, which binds to the riboswitch, the terminator appears to be destabilized and consequently~70 % of the transcript is full-length (Mandal et al, 2004). Glycine-dependent activation of this riboswitch has also been reported in other species (Sherman et al, 2012). We hypothesize that s B -dependent formation of glycine is responsible for activating transcription of the gcvT operon via this riboswitch, as we found lmo2539 (glyA; Group B, Table S2), which encodes a serine hydroxymethyltransferase that catalyses the interconversion of L-serine to glycine (Stauffer, 1996), to be positively regulated by s B .…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…In the presence of glycine, which binds to the riboswitch, the terminator appears to be destabilized and consequently~70 % of the transcript is full-length (Mandal et al, 2004). Glycine-dependent activation of this riboswitch has also been reported in other species (Sherman et al, 2012). We hypothesize that s B -dependent formation of glycine is responsible for activating transcription of the gcvT operon via this riboswitch, as we found lmo2539 (glyA; Group B, Table S2), which encodes a serine hydroxymethyltransferase that catalyses the interconversion of L-serine to glycine (Stauffer, 1996), to be positively regulated by s B .…”
mentioning
confidence: 82%
“…As one mechanism for post-transcriptional regulation is through riboswitches, we further evaluated the 59 UTR Mandal et al (2004); the leader-linker interaction is based on the data for lmo1348 provided by Sherman et al (2012). The terminator was identified using TransTermHP (Kingsford et al, 2007).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…When in water only, RNA is expected to be unstructured, and W-band spectrum ( Figure 4C top and S8) with a SNR value of 18:1 reveal disorder, with spectral simulation giving a correlation time of 0.4 ns. It has previously been shown that, upon addition of salts and ligands, the VC glycine riboswitch folds with formation of the kink turn [53,54,63,64] where, based upon comparisons to X-ray models of other k-turn motifs [65,66], the modified U2-base is expected to become base paired/base stacked. Hence, a decrease in dynamics (an increase in correlation time) is anticipated.…”
Section: Characterizing Conformational Dynamics In Large Rnasmentioning
confidence: 99%
“…Recently, two groups have independently provided a possible explanation for the unusually high divalent cation requirement of this RNA. Kladwang et al (2012) and Sherman et al (2012) found that the linker segment connecting the two aptamer domains, rather than being single-stranded, forms a hitherto unrecognized helix (P0 hereafter) with a conserved RNA segment 5 ′ to the first aptamer domain (Fig. 1A).…”
Section: Introductionmentioning
confidence: 99%